Association of LEPTIN and other inflammatory markers with preeclampsia: A systematic review - Veiga, Eduardo Carvalho de Arruda; Korkes, Henri Augusto; Salomão, Karina Bezerra; Cavalli, Ricardo Carvalho (Frontiers in Pharmacology, 2022)
Background: Preeclampsia is a serious pregnancy complication that affects 5%–10% of the obstetric population. Objective: To study inflammatory markers associated with preeclampsia. Search Strategy: Searches of articles on the topic published over a 10-year period (2009-2019) were performed in three databases (PubMed, Cochrane, and Embase) using the keywords preeclampsia and inflammatory markers. The PubMed search using 10 years and humans as filters retrieved 124 articles. Using an advanced search strategy, 0 articles were identified in Embase and 10 articles in Cochrane. After screening and eligibility assessment, 13 articles were included in the systematic review and meta-analysis. Meta-analysis and quality assessment of the studies were performed using the Review Manager 5.3 program. Results: For meta-analysis, women with preeclampsia were compared to control women, i.e., pregnancies without arterial hypertension. Leptin levels were significantly higher (p<0.0002) in women with preeclampsia compared to controls. Total cholesterol was also significantly elevated in women with preeclampsia (p<0.0001). There was no significant difference in HDL between groups, but women with preeclampsia had significantly increased LDL (p<0.01). The same was observed for triglycerides, which were significantly increased in women with preeclampsia (p<0.04) compared to controls. Analysis of TNF-alpha, an important inflammatory marker, showed higher levels in women with preeclampsia (p<0.03) compared to controls. The same was observed for another important inflammatory marker, interleukin 6, which was significantly increased in women with preeclampsia (p<0.0002). There was a significant increase of C-reactive protein in women with preeclampsia (p<0.003) compared to controls. Conclusion: Women with preeclampsia have increased levels of inflammatory markers compared to control women.